Pengurangan Emisi CO2 dari Pembangunan Rumah Berdasarkan Komponen Lingkungan Pendukung Berdasarkan Komponen Lingkungan Pendukung Rumah dan Kehidupan di Kampung Naga - Indira Kusuma Dewi (The Institute for Research and Community Services, Institut Teknologi Bandung, 2007)
Kampung Naga in West Java is well-known place of living that preserve its traditional values. Houses in Kampung Naga mainly made of bamboo and woods construction. An interviewand field observation are conducted to know the components of their traditional heousing constructions as well as their lifestyle. Some information is then traslated into CO2 emission that found equal to 3kg, a quite law emission. This is due to the fact that they use the materials from its surrounding environment under a strict rule of the group led by a key-person of the group.